Les mouvements dans l'espace des éléments linéaires - Urbonas, A. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Урбонас. Движения в пространстве линейных элементов общей аффинной связностиA. Urbonas. Judesiai tiesinių elementų erdvėje su bendru afininiu sąryšiu